Origin, local dispersal, and reproductive patterns of the bait polychaete, Diopatra aciculata Knox and Cameron, 1971 (Annelida: Onuphidae), in the Knysna Estuary, South Africa - Schoeman, Stephanie (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.